RETRACTED: microRNA‐383 suppresses the PI3K‐AKT‐MTOR signaling pathway to inhibit development of cervical cancer via down‐regulating PARP2. Issue 7 (25th March 2018) - Teng, Peng; Jiao, Yan; Hao, Min; Tang, Xin
Abstract: This study aims to evaluate the effect of the regulatory relationship between microRNA‐383 (miR‐383) and PARP2 in the cell migration and invasion in human with cervical cancer (CC) via the PI3K‐AKT‐MTOR signaling pathway. Cancerous tissues and corresponding paracancerous tissues were collected from 115 patients with CC. The positive expression rate of PARP2 was detected by immunohistochemistry. HeLa cells with highest miR‐383 expression were selected and assigned into the blank, negative control (NC), miR‐383 mimic, miR‐383 inhibitor, si‐PARP2, and miR‐383 inhibitor + si‐PARP2 groups. qRT‐PCR and Western blot were performed to evaluate the expression of miR‐383, PI3K, AKT, mTOR, PARP2, and p70S6K. MTT assay were utilized to measure cell viability. Transwell assay were applied to evaluate cell invasion and metastasis. Dual luciferase reporter assay identified that PARP2 is a target gene of miR‐383. Cancerous tissues manifested higher expression of PI3K, AKT, mTOR, PARP2, and p70S6K but lower miR‐383 expression than paracancerous tissues. Compared with the blank and NC groups, the miR‐383 mimic and si‐PARP2 groups had decreased expression of PI3K, AKT, mTOR, PARP2, and p70S6K mRNA and protein. In the miR‐383 mimic and si‐PARP2 groups, the cell viability, migration, and invasion were descended, in comparison to the blank and NC groups. All above parameters showed an opposite trend in the miR‐383 inhibitor group when compared with the blank and NC groups. This study demonstrates that miR‐383 could down‐regulate PARP2 to protect against CC by inhibiting PI3K‐AKT‐MTOR signaling pathway. Abstract : This study demonstrates that miR‐383 could down‐regulate PARP2 to protect against CC by inhibiting PI3K‐AKT‐MTOR signaling pathway.